Comparison of Wildlife Protection Law between Indonesia and the United States - Apriyani, Lusi; Yoesmar AR, Fahmi; Erwandi, Marta (Faculty of Law, Hasanuddin University, 2018)
Indonesia is known as one of the richest countries for its biodiversity. Plants, animals, and forest are very diverse in every region in Indonesia. Unfortunately, from time to time the numbers of biodiversity have been decreased along with the development of Indonesia. Nowadays, numbers of Sumatera Tigers and Orang Utan are not more than 400 since they were traded, captured, and killed in the name of economic development. Even wildlife habitat, forest, were converted to non-forestry use. Theoretically, Indonesia has Conser-vation Act which is the Law Number 5 of 1990 on Conservation of Biodiversity and Ecosystem in which providing protection to the biodiversity. However, this law mostly talks about conservation system rather than providing legal protection to the wildlife and its habitat. In addition, the law seems to stand on its own, meaning only Biodiversity Law regulates protection to wildlife. Other acts like Forestry law, Environmental law, Plantation law, and Mining law do not provide wildlife protection. While both flora and fauna are the most vulnerable elements affected by activities which are regulated by those laws. The existence of the conditions above indicates that the legal protection of wildlife needs to be improved. One of the improvement efforts is to reform the Indonesian wildlife protection law. The law reform of Indonesia wildlife protection can be done through comparative approach toward legal framework of wildlife protection of Indonesian and United States.